2021
DOI: 10.1037/xge0001049
|View full text |Cite
|
Sign up to set email alerts
|

Child witness expressions of certainty are informative.

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 83 publications
3
12
0
Order By: Relevance
“…Positive confidence-accuracy relations within each age group were obtained both immediately after encoding when items could still be maintained within capacity-constrained WM, and following a much longer sequence of events, when information had to be retrieved from LTM. Our results replicate those of earlier findings in childhood development (Winsor et al, 2021), young adulthood (Wixted & Wells, 2017), and older adulthood (Colloff et al, 2017) documenting positive confidence-accuracy relations in LTM, albeit with variations in the strength of these relations across the lifespan (cf., Fandakova et al, 2013;Shing et al, 2009). Extending on these earlier studies, we found that similar confidence-accuracy relations arise in WM, the "gateway" through which new LTMs are formed (Forsberg, Guitard, Adams, et al, 2022;Forsberg, Guitard, & Cowan, 2021;Forsberg, Guitard, Greene, et al, 2022;Forsberg et al, 2023;Fukuda & Vogel, 2019;cf., Atkinson & Shiffrin, 1968;Cowan, 1988Cowan, , 2019Cowan et al, 2024).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Positive confidence-accuracy relations within each age group were obtained both immediately after encoding when items could still be maintained within capacity-constrained WM, and following a much longer sequence of events, when information had to be retrieved from LTM. Our results replicate those of earlier findings in childhood development (Winsor et al, 2021), young adulthood (Wixted & Wells, 2017), and older adulthood (Colloff et al, 2017) documenting positive confidence-accuracy relations in LTM, albeit with variations in the strength of these relations across the lifespan (cf., Fandakova et al, 2013;Shing et al, 2009). Extending on these earlier studies, we found that similar confidence-accuracy relations arise in WM, the "gateway" through which new LTMs are formed (Forsberg, Guitard, Adams, et al, 2022;Forsberg, Guitard, & Cowan, 2021;Forsberg, Guitard, Greene, et al, 2022;Forsberg et al, 2023;Fukuda & Vogel, 2019;cf., Atkinson & Shiffrin, 1968;Cowan, 1988Cowan, , 2019Cowan et al, 2024).…”
Section: Discussionsupporting
confidence: 91%
“…Because the LTM tests of the present study pertain to episodic memories (i.e., remembering specific items encountered in a specific time and place; Tulving, 1983), we hypothesized that older adults would be more prone to highconfidence LTM recognition errors than younger adults. A similar tendency toward high-confidence LTM errors may also be found among young children in the present study, particularly those aged 7 and younger (e.g., Winsor et al, 2021) but potentially also for children up to age 10 (e.g., Brewer & Day, 2005;Howie & Roebers, 2007). It is conceivable that these age-related high-confidence memory errors may not appear in tests of WM, where young children or older adults may be better able to access their specific representations of recently encoded information (e.g., .…”
Section: Hypotheses For Age Differences In the Confidence-accuracy Ma...supporting
confidence: 88%
See 2 more Smart Citations
“…Confidence ratings were used to further partition the data into three confidence subgroups: low = 0%-59%, moderate = 60%-89%, and high = 90%-100%. Most studies used a scale from 0% to 100% for confidence ratings, but one used a 5-point scale (Winsor et al, 2021), which we transformed to a scale from 0% to 100%.…”
Section: Methodsmentioning
confidence: 99%